Perbandingan Kinerja Keuangan Berdasarkan Laporan Laba Rugi, Neraca, dan Arus Kas antara PT Yamaha Indonesia Motor Manufacturing dan PT Citra Surya Pacific 2010-2024 - Fauziah, Rizka Dwi; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze and compare the financial performance of PT Yamaha Indonesia Motor Manufacturing and PT Citra Surya Pacific during the period 2010–2024 based on key financial variables, namely revenue, cost of goods sold (COGS), net profit, total assets, and total liabilities. The research employs a quantitative descriptive method with a comparative approach. The data used in this study are secondary data obtained from the companies' financial statements. The analysis technique involves comparing the development of each variable over the observed period to identify trends and differences in financial performance. The results show that PT Yamaha Indonesia Motor Manufacturing demonstrates more stable financial performance, with consistent growth in revenue and net profit. In contrast, PT Citra Surya Pacific experiences fluctuations, particularly in net profit and liabilities, indicating less efficient financial management. Furthermore, Yamaha shows stronger asset growth and a more balanced liability structure, reflecting better financial stability and operational efficiency.The findings of this study provide insights into the importance of effective financial management and operational efficiency in maintaining sustainable company performance. This research can be used as a reference for investors, management, and academics in evaluating and comparing corporate financial performance. .